5 letku v 4 goda – vypolnim! - Ivanov, Viktor Semonovich (Советский Полический Плакат, 1948)
Soviet worker with shovel and goggles working Original title: 5 летку в 4 года – выполним! Suggested translation: 5-year plan in 4 years – we can do it! PO-0065